Optimasi Penggunaan Data Logger Pada Internal Kendaraan Berbasis IOT - Edo Roska; Taufiq; Rosdiana Rosdiana; Selamat Meliala (Jurnal Minfo Polgan, 2023)
Abstract―Vehicles are a secondary need for humans that can be postponed. However, Indonesia has a tropical climate, so everyone needs a vehicle as a means of transportation, therefore every year vehicles increase rapidly as the population increases. Indonesia is currently a fairly large vehicle sales market. So with the increasing number of road vehicles getting out of control, the result is congested roads, as a result of which traffic violations and accidents are increasing every year. Therefore, by making an optimization tool for using data loggers on two-wheeled vehicles, we intend to monitor every vehicle on the road. However, this research focuses on output data such as accuracy and delay of real time IoT-based vehicle data and data loggers that are stored automatically on SD memory cards in two-wheeled vehicles. The research results from the Infrared sensor data sent to the Blynk server, there is a fairly long delay and the data stored on the SD memory card is quite good, only has a delay per one second, the voltage sensor here plays a good role in real time data and data on the SD memory card because there is no delay the old ones are in sync with actual events, while the realtime control panel output results to the Blynk server using the NodeMCU ESP8266 produce realtime output, and the use of relays as controllers of the tools that have been made has been tested and obtained satisfactory results.